2003
DOI: 10.4049/jimmunol.171.12.6406
|View full text |Cite
|
Sign up to set email alerts
|

Newly Activated T Cells Promote Maturation of Bystander Dendritic Cells but Not IL-12 Production

Abstract: The activation of dendritic cells (DC) leads to increased costimulatory activity (termed DC maturation) and, in some instances, production of immunomodulatory cytokines such as IL-12. Both innate and T cell-derived signals can promote DC activation but it is unclear to what extent the two classes of stimuli are interchangeable or regulate distinct aspects of DC function. In this study, we show that signals from newly activated CD4+ T cells cannot initiate IL-12 synthesis although they can amplify secretion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 54 publications
3
41
1
Order By: Relevance
“…These observations reveal that dedicated Th cell polarization has indeed an impact on some but not all DC biological responses. These results extend previously published data showing that coculture of DCs with Th cells, gd T cells, or NK cells activates DCs to IL-12 production (24,25,34,35), whereas upregulation of costimulatory molecules by DCs can be triggered in the absence of direct T cell/DC contact (25,24).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These observations reveal that dedicated Th cell polarization has indeed an impact on some but not all DC biological responses. These results extend previously published data showing that coculture of DCs with Th cells, gd T cells, or NK cells activates DCs to IL-12 production (24,25,34,35), whereas upregulation of costimulatory molecules by DCs can be triggered in the absence of direct T cell/DC contact (25,24).…”
Section: Discussionsupporting
confidence: 80%
“…3A), indicating that Th cell-driven DC upregulation of costimulatory molecules is uncoupled from Th cell polarization. In a second set of experiments, we investigated whether the inhibition of the PKCz pathway in T cells could inhibit IL-12 production by DCs, a function known to require the physical contact with Th cells (24,25). This analysis showed that DCs cultured with PKCz-PSpretreated Th cells released lower amounts of IL-12 when compared with DCs interacting with untreated T cells (Fig.…”
Section: Inhibition Of Pkcz Pathway In Th Cells Affects Il-12 Productmentioning
confidence: 99%
“…3). These results are in agreement with previously published data showing that the upregulation of surface activation markers by dendritic cells (DCs) requires neither dedicated Th cell polarization nor Th cell/DC contact (27)(28)(29).…”
Section: The Journal Of Immunologysupporting
confidence: 83%
“…Moreover, others and we have shown that the IS formation plays a key role in T/DC cross-talk (30,(35)(36)(37)(38). We thus examined the distribution of CD154 at the IS formed between human monocyte-derived DCs and autologous CD4…”
Section: Cd40l (Cd154) Expression By Both Murine and Human Cd4mentioning
confidence: 99%